Potensi Memajukan Perekonomian Desa Sukamaju Rancakalong Sumedang Melalui OVOP Jarenju - Purwadhi (UNISBA Press, 2024)
Abstract. It is recorded that in 2023, Sukamaju Village, Rancakalong District, Sumedang Regency has 4,622 total inhabitants, the productive land area is rice fields and agriculture, and one of the other potentials is to have a palm starch factory with 7 factory locations with an estimated production of 10 tons of palm sugar per month. With the background of the initiative to maintain and promote ginger farming, where these crops constitute the majority of commodities from Sukamaju Village, the concept of One Village One Product (OVOP) needs to be encouraged. Jarenju is a superior product that stands for